Is a Pedagogy of Indigenous Solidarity Possible in the International Relations Theory Classroom? - Khalid, Maryam; McMillan, Mark; Symons, Jonathan (International Studies Perspectives, 2021)
Abstract How should teachers of international relations in settler-colonial states engage with First Nations’ sovereignty claims? While a growing body of recent scholarship explores how teaching might acknowledge and move beyond the discipline's racist and colonial origins, less research investigates how pedagogy might rectify inattention to Indigenous sovereignty. This paper reports on a class activity that sought to highlight how the discipline's foundational assumptions can naturalize Indigenous dispossession. In the class, students were asked to conduct discourse analysis of debates surrounding the “Uluru Statement from the Heart,” and to consider practices of Indigenous transnationalism. Although students generally succeeded in identifying how discursive practices consolidate the authority of the settler-colonial state, class discussion tended to reproduce the state's justificatory narratives and to classify First Nations’ claims as akin to those of any other ethnic minority. At a time when many universities are seeking to embed more Indigenous content within curriculum, we reflect on how the activity revealed epistemic colonialism's operation within educational settings. We argue that in addition to introducing Indigenous perspectives and knowledges, it is valuable for teaching in settler-colonial states to focus critical attention onto non-Indigenous practices that reproduce systemic injustice.